The Role of Accounting Information Systems in Management Decision Making at PT. Jaya Construction Bumi Karsa KSO North Luwu Regency - Yenni Yuniarti; Mukminati Ridwan; Wahyuni (IECON: International Economics and Business Conference, 2024)
This study aims to explore the role of accounting information systems (AIS) in supporting management decision-making at PT. Jaya Kontruksi-Bumi Karsa KSO in North Luwu Regency. The research adopts a qualitative approach, utilizing data collection techniques such as observation, interviews, and documentation. The findings highlight that the accounting information system at PT. Jaya Kontruksi-Bumi Karsa KSO plays a crucial role in enhancing decision-making processes. The system is found to be both effective and efficient, allowing management, particularly company managers, to access accurate and timely financial information. This, in turn, facilitates informed decisions, improves operational efficiency, and supports better resource allocation. The study underscores the importance of a well-structured AIS in providing relevant data that can guide strategic and tactical decisions within the organization. It also suggests that the use of advanced accounting information systems can significantly improve the overall management process by ensuring that decisions are based on reliable financial data. These findings emphasize the need for companies to continuously improve their accounting information systems to maintain competitiveness and optimize management decisions. Future research could investigate the integration of AIS with other business systems and the long-term impact on organizational performance.